Cell proliferation of HaCaT keratinocytes on collagen films modified by argon plasma treatment - García, Jorge López; Asadinezhad, Ahmad; Pacherník, Jirí; Lehocký, Marián; Junkar, Ita; Humpolícek, Petr; Sáha, Petr; Valásek, Pavel (Molecules (Basel, Switzerland), 2010)
Argon plasma treatment was used to modify the surface of atelocollagen films using a plasmochemical reactor. To evaluate the effects of the treatment, the untreated and treated samples were characterized by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), Scanning Electron Microscopy (SEM) imaging, and X-ray Photoelectron Spectroscopy (XPS) techniques. Cell growth was carried out by culturing human immortalized keratinocyte (HaCaT) cells and proliferation was measured via MTT assay. It was observed that argon plasma treatment significantly enhanced the extent of cell proliferation, which was ascribed to the favourable role of plasma treatment in inducing surface oxygen-containing entities together with increasing surface roughness. This can be considered as a potentially promising approach for tissue regeneration purposes.
Keywords: Humans; Photoelectron Spectroscopy; fotoelektronová spektroskopie; Keratinocytes; keratinocyty; Microscopy, Electron, Scanning; lidé; kolagen; proliferace buněk; Argon; Collagen; buněčné linie; spektroskopie infračervená s Fourierovou transformací; Cell Line; Spectroscopy, Fourier Transform Infrared; mikroskopie elektronová rastrovací; Cell Proliferation; argon; regenerace; Cell Culture Techniques; Regeneration; buněčné kultury